Implementasi Filsafat Perenialisme: Studi Kasus Pembentukan Karakter Religius Siswa SDN Tanah Kalikedinding II Surabaya - Yuniar, Kamelia Nobella; Rossydah, Ninin Indira; Wijaya, Bagus Rahmad (Jurnal Riset Madrasah Ibtidaiyah, 2025)
This study aims to explore the implementation of perennialist philosophy in shaping students' religious character at SDN Tanah Kalikedinding II Surabaya. Perennialism is grounded in the belief in eternal, universal truths embedded in religious teachings, classical ethics, and cultural traditions. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving fourth-grade teachers and students. The findings reveal three key practices: (1) Jumat IMTAQ (Friday Faith Development) through congregational dhuha prayers, which foster discipline and spiritual awareness; (2) the 3S culture (smile, greet, salute), which enhances mutual respect and social harmony; and (3) group prayer before class, which strengthens humility, spiritual focus, and reliance on God during learning. These practices function as concrete applications of perennialist values, contributing to the development of religious character, responsibility, and moral integrity in early education. The results demonstrate that perennialist values can be consistently and sustainably internalized through daily school activities. This study contributes to the advancement of science and technology (IPTEK) in character education by offering a philosophical and pedagogical model for integrating timeless values into early childhood education policy and practice.